The divorce process in Emirati society: A qualitative sociological approach from the perspective of the social process - Aljabri, Shaymaa; AlHourani, Mohammed (Al-Adab Journal, 2025)
This study aimed to explore the process of divorce in Emirati society through a qualitative sociological approach based on the perspective of the social process. Divorce is considered a significant social issue that goes beyond merely ending a marital relationship; it is a process that undergoes several complex stages, starting from marital conflicts and their negative impact on marital compatibility, and ending with final separation. In the initial stage, marital conflicts arise from accumulated issues and ineffective communication between spouses, which may include differences in values and perspectives, financial disputes, or life pressures. This tension negatively affects the marital relationship, leading to a deterioration of trust and mutual respect, making constructive dialogue difficult. Over time, these conflicts become significant obstacles that push the spouses toward considering divorce as a solution to regain psychological peace and stability.The descriptive-analytical method was used in this study to collect data from various sources such as interviews, surveys, and field observations. The researcher relied on the qualitative analysis tool (in-depth personal interviews), collecting data from 30 individuals who were divorced in the Emirate of Sharjah (19 females and 11 males). The statements and data collected were analyzed to provide a deeper understanding of the stages of the divorce process and how different factors affect the marital relationship.The study resulted in a comprehensive understanding of the stages involved in divorce, from the emergence of marital problems to the final decision to divorce. It also revealed that the gradual accumulation of unresolved issues and the lack of conflict resolution skills among spouses play a significant role in the progression of the relationship toward divorce.